2006
DOI: 10.1373/clinchem.2006.074724
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Micronized Fenofibrate on Carotid Atherosclerosis in Patients with Essential Hypertension

Abstract: Background:The coexistence of hypertension and dyslipidemia synergistically increases the risk of cardiovascular events. We investigated the effect of the lipidlowering agent micronized fenofibrate on inhibition of carotid atherosclerosis in patients with essential hypertension and mild hyperlipidemia. Methods: We measured serum lipid profiles and inflammatory markers on chemistry or immune analyzers and common or internal carotid intima-media thickness (IMT) and diameter (D) by ultrasonography.Results: Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
1
21
0
2
Order By: Relevance
“…Furthermore, in the LIPID Atherosclerosis Substudy (31), pravastatin reduced the carotid IMT in subjects with coronary heart disease. Zhu et al (32) have demonstrated that micronized fenofibrate inhibits the progression of carotid IMT in patients with hypertrigryceridemia and essential hypertension. Katakami et al (33) have shown that gliclazide attenuates progression of carotid IMT in subjects with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the LIPID Atherosclerosis Substudy (31), pravastatin reduced the carotid IMT in subjects with coronary heart disease. Zhu et al (32) have demonstrated that micronized fenofibrate inhibits the progression of carotid IMT in patients with hypertrigryceridemia and essential hypertension. Katakami et al (33) have shown that gliclazide attenuates progression of carotid IMT in subjects with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In DAIS (Diabetes Atherosclerosis Intervention Study), fenofibrate slowed progression of coronary atherosclerosis but did not significantly reduce cardiac end points (14). Studies with carotid intima-media thickness (IMT) as a surrogate end point have produced inconsistent results: one with slower progression of carotid atherosclerosis in patients on fenofibrate compared with placebo (15) and one with no effect of bezafibrate on IMT (16), whereas another study reported progression of atherosclerosis in patients on different fibrates compared with those on statins (17).…”
Section: See Page 2206mentioning
confidence: 99%
“…Opublikowana w 2015 roku analiza oparta na badaniu Framingham pokazała, że w ciągu 9-letniej prospektywnej obserwacji pacjentów nieobciążonych IS lub TIA HDL-C nie większe niż 40 mg/dl było związane z podwyższonym ryzykiem udaru niedokrwiennego ([95% CI] 1,59 [1,23-2,05]; p < 0,001), natomiast stężenie TG nie wpływało na ryzyko IS [53]. Badanie to potwierdziło wcześniejsze analizy, według których na każdy wzrost stężenia HDL-C o 1 mmol/l ryzyko IS zmniejsza się rocznie o 11-15% [10].…”
Section: Fibraty W Neurologiiunclassified